Mortality predictors, hepatic involvement patterns, and the steatotic liver paradox in 1,484 hospitalized Dengue patients - Aryalakshmi Sreemohan; Arif Hussain Theruvath; Ambily Baby; Cyriac Abby Philips; Tharun Tom Oommen; Santhichandra Pai; Salini Baby John; Jaicob Varghese; Rizwan Ahamed; Ajit Tharakan; Philip Augustine (PLoS ONE, 2026)
Background and objectives Dengue fever represents a major global health burden with hepatic involvement occurring in up to 90% of hospitalized patients. This study aimed to determine in-hospital mortality predictors, characterize clinical outcomes across graded hepatic injury phenotypes, and validate prognostic scoring systems in hospitalized dengue patients. A primary focus was assessing the impact of pre-existing liver conditions on disease trajectory and survival. Methods A retrospective cohort analysis was conducted on 1,484 patients with laboratory-confirmed dengue infection admitted to a tertiary-care center between 2021 and 2024. Patients were stratified by hepatic status into those with pre-existing chronic liver disease, non-chronic steatotic liver involvement, and no liver involvement. Multivariable logistic regression identified independent mortality predictors, while unsupervised clustering distinguished clinical phenotypes. The performance of physiological and liver-specific prognostic scores was evaluated against clinical outcomes. Results The overall in-hospital mortality rate was 5.1%, with 13.1% requiring intensive care admission. Independent predictors of mortality included severe dengue classification, intensive care unit admission, elevated neutrophil-to-lymphocyte ratio, and hypoalbuminemia, with albumin emerging as the strongest single biomarker for risk prediction. Paradoxically, patients with steatotic liver disease demonstrated improved survival compared to those without pre-existing liver disease, supporting an “obesity paradox” in this tropical infection context, whereas decompensated cirrhosis was associated with markedly adverse outcomes. The Albumin-Bilirubin grade successfully stratified hepatic risk, and the Simplified Acute Physiology Score-3 significantly outperformed the Sequential Organ Failure Assessment for predicting mortality in critically ill patients. Four distinct clinical phenotypes with differential mortality ranging from 3.0% to 100% were identified. Conclusions Hypoalbuminemia serves as a critical, accessible prognostic marker in dengue fever. Pre-existing liver pathology demonstrates divergent impacts on outcomes, with steatotic liver disease potentially conferring survival advantage contrary to traditional metabolic risk assumptions. These findings support the utility of liver-specific scoring systems for acute risk stratification in dengue-endemic regions.